Konvensi Penghapusan Segala Bentuk Diskriminasi terhadap Wanita dalam Persepsi dan Kenyataan Sosial - Sulistyowati Irianto; Tri Trisnohandoko (Antropologi Indonesia, 1992)
In November 1967 the General Assembly United Nations adopted the declaration "to ensure the universal recognition in law and in fact of the principle of equality of men and women". That Declaration was known as the Declaration of the Elimination of all forms of Discrimination against Women. One of the state ratified the declaration is Indonesia. The ratification was declared as Undang-undang No. 7/1984. After eight years declared, it would be still interesting to know how the law works in reality. Does anyone know about what happened and what is going on with the legal issues regarding women. This article tries to get some explanation about how far the declaration is known and what was done about it. Some law and social-political science students of University of Indonesia were interviewed. What they say, feel, and think about all of women issues in terms of knowing and understanding the declaration would be held in this small-scale research.